Meningkatkan Civic Engagement Siswa Melalui Pelibatan Aktif Dalam Program Sosial-Kultural Desa Semangat Dalam - Sigit Triyono; Said M. Ragil Al Bahasyim; Nurul Hidayahe; Rahmawati Rahmawati; Rezky Anisa; Riska Aulia; Nor Aida; Nor Andini; Erischa Marsela; Muhammad Azriel Akbar (Haumeni Journal of Education, 2026)
Education plays a strategic role in fostering civic engagement among students as a form of awareness and active involvement in social and community life. However, learning in schools still tends to focus on academic aspects, so that students' social experiences have not developed optimally. This study aims to describe efforts to increase student civic engagement through active involvement in socio-cultural programs in Semangat Dalam Village. The study uses a qualitative approach with a descriptive qualitative method to gain an in-depth understanding of the processes, experiences, and interactions of students in the village's socio-cultural activities. Data collection techniques were carried out through observation, direct participation, and documentation of activities. The results show that student involvement in socio-cultural activities, particularly participatory environmental and waste management programs, can increase students' social awareness, environmental concern, and responsibility towards their community. Students showed enthusiasm and active participation in activities, which was reflected in behavioral changes in maintaining environmental cleanliness and involvement in social activities. In addition, direct interaction with the village community provided contextual experiences that strengthened their understanding of the values of citizenship, cooperation, and mutual assistance. These findings indicate that village socio-cultural programs can be an effective vehicle for contextual learning in building sustainable civic engagement among students.